Specific Characteristics of Double Fertility Simmental Cattle (Cows) Imported To Karakalpakstan - Kazakbaev Bakht Seylbekovich; Naurizov Tokhtamis Kidirbergenovich; Shernazarov Saparbay Jumanazarovich (Scholars Digest Publishing, 2023)
The article provides information about the natural economic conditions of the "Koniratbay Mekhri" livestock farm, where experiments and methods of effective use of Simmental cattle brought to Karakalpakstan from Germany are carried out.
Keywords: Lactation, milk, Simmental, breed, genetics, innovation, dairy cow, productivity.